The overhauls technical innovation project optimization method of power grid device based on Life Cycle Asset Management. (December 2020) - Li, Na; Wang, Xiaoliang; Li, Chengqi; Zhang, Zhenjun; Zhang, Weiwei
Abstract: In order to realize the precise management of investment in equipment overhauls technical innovation project, this paper fully analyzed the cost characteristics of equipment in every section of the life cycle and established the actual available Life Cycle Cost (LCC) model and provided a combination forecasting method to forecast the future costs. Then this paper obtained the full life cycle cost of the equipment for overhauls technical innovation project. By comparison of the two average annual LCC costs of overhaul and technical innovation project, the final optimization project with the best economic benefit could be determined. Case analysis verified the economics of the method, which could provide decision support for precise investment in the power grid.